The committee has/have decided ... On concord patterns with collective nouns in inner- and outer-circle varieties of English - Hundt, Marianne (Journal of English linguistics, 2006)
Standard English is not a monolithic entity but shows systematic variation in terms of regional or stylistic preferences and ongoing change. The corpus-based approach has been used to study these patterns of variation in a number of so-called inner-circle varieties. Linguists have only recently started to collect data on variation in outer-circle varieties. The cumulative evidence from a number of such studies will eventually allow us to determine whether these varieties are still oriented toward exonormative models or whether they are developing internal (endonormative) models of usage. This article aims to contribute to this field of research by investigating one syntactic variable— concord with collective nouns—in two outer-circle varieties: Singaporean English, which is British-based, and Philippine English, which is American-based. For both varieties, components of the International Corpus of English are examined. The results show that neither Singaporean nor Philippine English patterns exactly like its “parent” variety.